Microstructure on the TiB and Mg Reinforced of Al356 Alloy with Die Casting Process - E I Bhiftime (Biomedical and Mechanical Engineering Journal (BIOMEJ), 2022)
Abstract. Metal matrix composites (MMC) reinforced with titanium boron and magnesium offer high mechanical and good physical. Al356 alloy reinforced with TiB and Mg particles in die casting prosses was the most simple way. The purpose of the study was to investigate the difference of the microstructure to Al356 alloy reinforced of TiB and Mg particles, as well as the changing effects on the extra level of TiB and Mg. The base materials used were Al356 alloy as the matrix and TiB and Mg as the reinforcement (3, 4, 5 wt%). The casting prosses used in the study was the die casting. The microstructure of the composites fabricated by different parameters indicated that semi-solid method resulted improved in homogeneous particle distribution 3–5 wt% TiB and Mg composites were fabricated by the novel processing. The particle distribution was uniform in these composites. Grain sizes of composites will be much smoother by giving TiB. The Grain sizes of were enhanced as the particle contents increased. The morphology of the composite between the reinforcing particle to the Al356 alloy matrix was to unite and to be dispersed evenly. This article only discusses micro and SEM.